Molecular phylogeny of Menonvillea and recognition of the new genus Aimara (Brassicaceae: Cremolobeae). Issue 6 (1st December 2013) - Salariato, Diego L.; Zuloaga, Fernando Omar; Al-Shehbaz, Ihsan A.
Abstract: Monophyly and phylogeny of Menonvillea were studied using molecular phylogenetic analyses of nuclear ribosomal (ITS) and chloroplast (trnL–F) DNA sequences. The phylogenies obtained were contrasted with the morphology of the genus. Menonvillea, excluding M. rollinsii, is monophyletic, and this species is sister to Cremolobus. Molecular and morphological data support the segregation of M. rollinsii into the new genus Aimara. Within the Menonvillea clade, three strongly supported and morphologically well–defined lineages were obtained. The geographical distribution of Aimara and the Menonvillea lineages are discussed.